Method-comparison studies in telehealth: Study design and analysis considerations. (October 2017) - Russell, Trevor G; Martin-Khan, Melinda; Khan, Asaduzzaman; Wade, Victoria
When establishing telehealth services, clinicians need to be confident that the examinations, assessments and clinical decisions that they make while using technology are equivalent to conventional best practice. Method-comparison studies are ideally suited to answering these questions, however there is a lack of consistency in the telehealth literature in the study methodologies and data analysis techniques used. Methodologies should closely match clinical practice to maximise external validity and data analysis techniques should match the data types generated in order to be clinically meaningful. In this article we discuss the design, analysis and interpretation of method-comparison studies in the context of telehealth research.